Book review: Challenging the conventional wisdom about residential care of the children and youth: a good place to grow by Bruce B. Henderson - James P. Anglin (Scottish Journal of Residential Child Care)
I need to be clear that I do not come to this review as a dispassionate or objective reviewer. Quite the opposite. I have been an advocate for the premise of this text for a great many years, and I was engaged with the author as an informal advisor as he wrote this book. However, I believe this is an important and timely text that deserves to be widely read by all those involved in the residential child care system, at any level, and in any jurisdiction. To my mind, this book is overdue. It offers a rigorous examination of over 400 references from the international literature on the provision of residential care for young people, undertaken by an expert in research methodology with an open and curious mind about what the evidence tells us about the effectiveness of residential care for children and youth.